Composite positive electrode material for lithium ion battery, preparation method and battery

By adding 5%-15% sacrificial agent in the preparation process of composite positive electrode materials, the problems of high interface impedance and side reactions in solid-state lithium-ion batteries are solved, and composite positive electrode materials with high electrochemical activity and stable structure are achieved, improving the performance of lithium-ion batteries.

CN119695071AActive Publication Date: 2025-03-25UNIV OF SCI & TECH BEIJING
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411882082.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In solid-state lithium-ion batteries, the interface impedance between the solid-state electrolyte and the positive electrode material is high, resulting in low electrochemical performance of the battery, and side reactions are prone to occur during high-temperature co-firing, resulting in structural collapse.

Method used

When preparing composite positive electrode materials, add 5%-15% sacrificial agents (such as lithium hydroxide, lithium carbonate or lithium oxalate) to prevent diffusion and side reactions between the positive electrode materials and solid electrolyte materials and improve interface contact and wettability.

Benefits of technology

By adding sacrificial agent, the electrochemical activity of the composite positive electrode material is significantly improved, the occurrence of side reactions is reduced, the structure is stabilized, and the overall performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695071A_ABST
    Figure CN119695071A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive electrode material for a lithium ion battery, a preparation method and the battery, and belongs to the technical field of lithium ion batteries. Comprising the following steps that positive electrode material powder and solid electrolyte powder are weighed and mixed, a mixture A is obtained, a designed positive electrode material and a designed solid electrolyte material are oxides, and the lithium ion concentration difference is not smaller than 0.012 mol / ml; a sacrificial agent is added into the mixture A and mixed, a mixture B is obtained, and the adding amount of the sacrificial agent is 5%-15% of the mass of the mixture A; and sintering the mixture B to obtain the composite material. By adding the sacrificial agent, generation of byproducts in the sintering process between the positive electrode material and the solid electrolyte material is avoided, and especially when the lithium ion concentration difference between the positive electrode material and the solid electrolyte material is not less than 5%, element diffusion in the sintering process becomes a non-negligible important factor for reducing the electrochemical performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite positive electrode material for lithium ion batteries, a preparation method and a battery. Background Art

[0002] In order to reduce the use of fossil fuels such as petroleum, the market for battery-powered electric vehicles has begun to expand. Replacing fuel vehicles that use non-renewable energy with electric vehicles is undoubtedly a future trend. At present, most electric vehicles on the market use batteries based on traditional liquid lithium-ion batteries. However, the liquid electrolyte in liquid lithium-ion batteries is a flammable organic solvent, which is prone to serious side reactions with electrodes, resulting in serious safety hazards such as battery fire or explosion, which undoubtedly poses a challenge to the application of lithium-ion batteries. Replacing the liquid electrolyte in traditional lithium-ion batteries with non-flammable solid electrolytes can greatly improve the safety of batteries. On the other hand, since lithium dendrites will pierce the diaphragm and cause a short circuit between the positive and negative electrodes of the battery, traditional liquid lithium-ion batteries cannot use lithium metal as the negative electrode, and can only use graphite with lower volume and mass energy density than lithium metal as the negative electrode. Solid electrolytes have higher mechanical strength and are not easily pierced by lithium dendrites, which can prevent the positive and negative electrodes from contacting and short-circuiting, making it possible for solid-state lithium-ion batteries to use metallic lithium as the negative electrode, thereby improving the energy density of lithium-ion batteries. Since the use of solid-state electrolytes can improve the safety and energy density of lithium-ion batteries, solid-state lithium-ion batteries are being widely studied as the next stage of development of lithium-ion batteries.

[0003] There are two key bottlenecks in the development of solid-state lithium-ion batteries. The first bottleneck is that the ionic conductivity of solid electrolytes is relatively low, which is several orders of magnitude lower than that of liquid electrolytes at room temperature. In the past few decades, people have been committed to designing solid electrolytes with better performance. The ionic conductivity of solid electrolytes has been continuously improved, and the lithium ion conductivity of some solid electrolytes is even comparable to that of liquid electrolytes. However, in traditional liquid lithium-ion batteries, the electrolyte can penetrate into the pores of the electrode to form a close solid-liquid interface contact. For solid-state lithium-ion batteries, since solid electrolytes have high mechanical strength and are not easy to deform, it is difficult for solid electrolytes to form a close solid-solid contact with electrodes, resulting in high interface impedance, which has become another bottleneck restricting the development of all-solid-state lithium-ion batteries. In order to improve the interface contact problem between the solid electrolyte and the positive electrode, it is usually necessary to prepare a composite positive electrode with the positive electrode active material. Smaller solid electrolytes can fill the gaps between the particles of the positive electrode active material, increase the interface contact area, and play a role in lithium ion transmission, thereby reducing the interface impedance.

[0004] For oxide solid electrolytes, due to their high hardness and rigidity, they are not easily deformed, so the composite cathode needs to be co-fired at high temperature to further promote solid-solid contact between the interfaces. Although high-temperature co-firing can promote solid-solid contact, it is easy to cause side reactions between the cathode active material and the solid electrolyte during the co-firing process, resulting in the collapse of the composite cathode structure and greatly reducing the electrochemical performance of the composite cathode. Summary of the invention

[0005] To solve the above problems, the present invention provides a composite positive electrode material for lithium-ion batteries, a preparation method and a battery. By adding a sacrificial agent, the generation of by-products between the positive electrode material and the solid electrolyte material during the sintering process is avoided. Especially when the difference in lithium ion solubility between the positive electrode material and the solid electrolyte material is not less than 5%, the diffusion of elements during the sintering process has become an important factor that cannot be ignored in reducing the electrochemical properties of the material.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] On the one hand, the present invention provides a method for preparing a composite positive electrode material for a lithium ion battery, comprising the following steps: weighing positive electrode material powder and solid electrolyte powder and mixing them to obtain a mixture A, wherein the designed positive electrode material and solid electrolyte material are oxides and the difference in lithium ion concentration is not less than 0.012 mol / ml; adding a sacrificial agent to the mixture A and mixing them to obtain a mixture B, wherein the amount of the sacrificial agent added is 5%-15% of the mass of the mixture A; and sintering the mixture B to obtain.

[0008] Furthermore, the designed positive electrode material is one or more of NCM, lithium cobalt oxide or lithium iron phosphate.

[0009] Further, the NCM is LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2 or LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0010] Furthermore, the designed solid electrolyte material is lithium aluminum titanium phosphate.

[0011] Furthermore, the designed mass ratio of the positive electrode material to the solid electrolyte material is 7:(2.8-3.2). Weigh the positive electrode material powder and the solid electrolyte powder.

[0012] Furthermore, the sacrificial agent is lithium hydroxide, lithium carbonate or lithium oxalate.

[0013] Furthermore, the average particle size of the sacrificial agent does not exceed 0.8 μm.

[0014] Furthermore, the sintering process is: in an oxidizing atmosphere, keeping the temperature at 600-700° C. for 0.5-1.0 h.

[0015] On the other hand, the present invention provides a composite positive electrode material, which is prepared by the above-mentioned preparation method.

[0016] On the other hand, the present invention provides a lithium ion battery, wherein the positive electrode of the lithium ion battery is prepared using the above-mentioned composite positive electrode material.

[0017] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include:

[0018] The present invention prepares a lithium-ion battery with high electrochemical activity through the above-mentioned preparation method. Specifically, the oxide-type solid electrolyte material includes multiple materials, such as LLTO, LLZO and LATP. In comparison, LATP does not use rare earth metals, so the cost is lower, but the stability of LATP is poor. In addition, since the difference in lithium ion concentration between the positive electrode material and the solid electrolyte material is not less than 0.012 mol / ml, the diffusion of elements is serious, and by-products such as Co3O4 and NiO are easily generated at the interface. Based on the above problems, the present application proposes adding 5%-15% sacrificial agent to the mass of mixture A. First, the mutual diffusion between the positive electrode material and the solid electrolyte material is prevented to cause the generation of by-products. Secondly, the sacrificial agent has a high lithium content and can supplement the lithium burn-off during the sintering process. Thirdly, the sacrificial agent can be used as a modifier of the interface between the positive electrode material and the solid electrolyte material, thereby improving the wettability of the interface between the positive electrode material and the solid electrolyte material during the sintering process, and comprehensively improving the electrochemical activity of the prepared lithium-ion battery. Finally, in the subsequent sintering process, the sacrificial agent needs to be completely decomposed or absorbed, otherwise the residual sacrificial agent will reduce the electrochemical activity of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 XRD diagrams of the dual-phase composite positive electrode materials prepared in Examples 1-3 and Comparative Example 1 of the present invention;

[0021] Figure 2The first cycle charge and discharge curves of the lithium ion batteries prepared in Examples 1-3 of the present invention and Comparative Example 1 at 0.1C;

[0022] Figure 3 Long cycle diagram of lithium ion batteries prepared in Examples 1-3 of the present invention and Comparative Example 1 at 1C;

[0023] Figure 4 XRD diagrams of the dual-phase composite positive electrode materials prepared in Example 8 of the present invention and Comparative Example 2;

[0024] Figure 5 The first cycle charge and discharge curves of the lithium ion batteries prepared in Example 8 and Comparative Example 2 of the present invention at 0.1C;

[0025] Figure 6 Long cycle diagram of lithium ion batteries prepared in Example 8 of the present invention and Comparative Example 2 at 1C;

[0026] Figure 7 XRD diagrams of the dual-phase composite positive electrode materials prepared in Example 9 and Comparative Example 3 of the present invention;

[0027] Figure 8 The first cycle charge and discharge curves of the lithium ion batteries prepared in Example 9 and Comparative Example 3 of the present invention at 0.1C;

[0028] Fig. 9 Long cycle diagram of the lithium ion batteries prepared in Example 9 of the present invention and Comparative Example 3 at 1C. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] The present invention provides a method for preparing a composite positive electrode material for a lithium ion battery, comprising the following steps:

[0031] S1 Weigh and mix the positive electrode material powder and the solid electrolyte powder to obtain a mixture A, wherein the positive electrode material and the solid electrolyte material are designed to be oxides and the difference in lithium ion concentration is not less than 0.012 mol / ml;

[0032] S2 adding a sacrificial agent to the mixture A and mixing them to obtain a mixture B, wherein the amount of the sacrificial agent added is 5%-15% of the mass of the mixture A;

[0033] S3: sintering the mixture B to obtain.

[0034] The present invention prepares a lithium-ion battery with high electrochemical activity through the above-mentioned preparation method. Specifically, the oxide-type solid electrolyte material includes multiple materials, such as LLTO, LLZO, ZZATO and LATP. In comparison, LATP, i.e. lithium aluminum titanium phosphate, does not use rare earth metals and has a lower cost, but LATP has poor stability. In addition, since the difference in lithium ion concentration between the positive electrode material and the solid electrolyte material is not less than 0.012 mol / ml, the diffusion of elements is serious, and by-products such as Co3O4, NiO and Fe2O3 are easily generated at the interface. Based on the above problems, the present application proposes adding 5%-15% sacrificial agent to the mass of mixture A. First, the mutual diffusion between the positive electrode material and the solid electrolyte material is prevented to cause the generation of by-products. Secondly, the sacrificial agent has a high lithium content and can supplement the lithium burn-off during the sintering process. Thirdly, the sacrificial agent can be used as a modifier of the interface between the positive electrode material and the solid electrolyte material, thereby improving the wettability of the interface between the positive electrode material and the solid electrolyte material during the sintering process, and comprehensively improving the electrochemical activity of the prepared lithium-ion battery. Finally, in the subsequent sintering process, the sacrificial agent needs to be completely decomposed or absorbed, otherwise the residual sacrificial agent will reduce the electrochemical activity of the lithium-ion battery.

[0035] Preferably, the difference in lithium ion concentration between the positive electrode material and the solid electrolyte material is not less than 0.025 mol / ml, 0.030 mol / ml, 0.035 mol / ml, or 0.040 mol / ml.

[0036] It should be noted that the positive electrode material powder and solid electrolyte powder in this application and the designed positive electrode material and solid electrolyte material can be the same or different. Specifically, if the positive electrode material powder or solid electrolyte powder uses the same material as the powder after final firing, the positive electrode material powder and solid electrolyte powder and the designed positive electrode material and solid electrolyte material are the same, otherwise they are different. Taking the positive electrode material as an example, if the designed positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O2, and the added positive electrode material powder is LiNi 0.8 Co 0.1 Mn 0.1 O2, then the two are the same. If the added positive electrode material powder is a hydroxyl type or other components, it can be prepared into LiNi after sintering. 0.8 Co 0.1 Mn 0.1 O2 material, the positive electrode material powder is different from the designed positive electrode material. For illustration, in the subsequent invention embodiments, the positive electrode material powder and the solid electrolyte powder are selected to be the same as the designed positive electrode material and the solid electrolyte material.

[0037] The molar concentration of lithium ions is calculated as follows:Li / V, unit is mol / L, where n Li is the molar number of lithium ions, and V is the volume of the solid phase material.

[0038] The mixing process is to mix by ball milling or grinding to improve the uniformity of the mixing. In the embodiment of the present invention, ball milling is preferably used for mixing. The mixing process is: the material-to-ball ratio is 0.9-1.1, the rotation speed is 200-300r / min, and the ball milling is at least 30h.

[0039] Specifically, the designed positive electrode material is one or more of NCM, lithium cobalt oxide or lithium iron phosphate. Preferably, the NCM is LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2 or LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0040] Specifically, the designed solid electrolyte material is LATP. Preferably, Li 1.3 Al 0.3 Ti 1.7 (PO3)4, compared with other oxide-type solid electrolyte materials, this material does not require the addition of rare earth metals, so the cost of preparing a solid-state lithium-ion battery is low, but the material has poor stability and is easily decomposed during the sintering process, and the lithium content of this material is low. The lithium molar concentration difference between this material and the positive electrode material is as high as 0.042 mol / ml, so it is more likely to cause element diffusion to produce by-products, resulting in low chemical activity of the prepared battery. For illustration, the embodiment of the present invention uses LATP for illustration.

[0041] Specifically, the designed mass ratio of the positive electrode material to the solid electrolyte material is 7: (2.8-3.2) Weigh the positive electrode material powder and the solid electrolyte powder. The mass ratio of the positive electrode material to the solid electrolyte material affects the chemical activity. The solid electrolyte material is a fast ion conductor. If the fast ion conductor forms a path in the positive electrode material, the electrochemical activity is higher. Therefore, it is necessary to strictly control the ratio of the positive electrode material to the solid electrolyte material to increase the probability of forming a path.

[0042] Specifically, the sacrificial agent is lithium hydroxide, lithium carbonate or lithium oxalate. Specifically, lithium hydroxide (LiOH), lithium carbonate (Li2CO3), lithium oxalate (Li2C2O4). It should be noted that when LiOH·H2O is used as a sacrificial agent, the mass of bound water needs to be added on the basis of the calculated mass of LiOH. For example, when the mass of LiOH is calculated to be 75 mg, the mass of LiOH·H2O to be added is 131.3 mg. The average particle size of the sacrificial agent does not exceed 0.8 μm. First, the size of the sacrificial agent particle size affects its interfacial energy and thus affects its activity during the sintering process. Secondly, the use of this particle size and the corresponding ratio can satisfy the requirement that the sacrificial agent is completely decomposed or absorbed in the subsequent preparation process, and there is no independent sacrificial agent phase; the sacrificial agent has a high lithium concentration and its cost is relatively high. The present invention, on the premise of adding less sacrificial agent, combines the particle size and the sintering process to prepare a composite positive electrode material that meets the purpose of the present invention. In order to further improve the electrochemical activity of the prepared composite positive electrode material, the average particle size of the positive electrode material is preferably 4-20 μm, the average particle size of the solid electrolyte material is 1-5 μm, and the average particle size of the sacrificial agent is not less than 0.2 and not more than 0.8 μm. When the particle size is too small, on the one hand, agglomeration is more serious and the cost is higher, and on the other hand, the particle size is too large and the inhibition performance is poor.

[0043] Specifically, the sintering process is: in an oxidizing atmosphere, keep the temperature at 600-700°C for 0.5-1.0h, and then cool it, such as naturally cooling or cooling with the furnace. Preferably, the temperature is increased to 600-700°C at a heating rate of no more than 10°C / min.

[0044] An embodiment of the present invention further provides a composite positive electrode material, which is prepared by the above-mentioned preparation method.

[0045] An embodiment of the present invention further provides a lithium ion battery, wherein the positive electrode of the lithium ion battery is prepared by using the above-mentioned composite positive electrode material.

[0046] In the following embodiments:

[0047] XRD test: using Rigaku UltimaIV-185X-ray powder diffractometer from Japan Rigaku Corporation.

[0048] Half-cell assembly: The composite positive electrode materials prepared in the embodiments of the present invention and the comparative examples were slurried and coated with Super P and PVDF in a mass ratio of 80:10:10, and then cut into pole pieces with a diameter of 10 mm. Metal lithium was used as the negative electrode, and the electrolyte used was LB-363 electrolyte from Suzhou Duoduo Chemical Technology Co., Ltd., and the half-cells were assembled in an argon glove box.

[0049] Lithium-ion battery charge and discharge test: LiNi 0.8Co 0.1 Mn 0.1 O2 / Li 1.3 Al 0.3 Ti 1.7 The charge and discharge voltage range of the battery prepared by (PO3)4 composite positive electrode material is 2.8-4.5V, and the LiCoO2 / Li 1.3 Al 0.3 Ti 1.7 The charge and discharge voltage range of the battery prepared by (PO3)4 composite positive electrode material is 3.0-4.5V, LiFePO4 / Li 1.3 Al 0.3 Ti 1.7 The charge and discharge voltage range of the battery prepared by the (PO3)4 composite positive electrode material is 2.5-4.0V. Before the cycle test, it is activated for three cycles at 0.1C, and then the charge and discharge cycle test is carried out at 1C using the same voltage range. All electrochemical performance tests are carried out at room temperature.

[0050] In order to better illustrate the embodiments of the present invention, the present invention is further described in detail below through specific examples.

[0051] Example 1

[0052] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0053] S1 weighs LiNi with a mass ratio of 7:3 0.8 Co 0.1 Mn 0.1 O2 powder and Li 1.3 Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiNi 0.8 Co 0.1 Mn 0.1 O2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.039 mol / ml.

[0054] S2 adds LiOH·H2O to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added LiOH·H2O is 15% of that of the mixture A.

[0055] S3: The mixture B is co-fired at 700° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as NCM811 / LATP-1.

[0056] The prepared NCM811 / LATP-1 was subjected to XRD detection. Figure 1 As shown in the figure, the peak intensity and position of NCM811 remain unchanged, indicating that the addition of the sacrificial agent inhibits the side reactions of the dual-phase composite cathode during high-temperature co-firing, stabilizes the structure of the dual-phase composite cathode, and there is no sacrificial agent phase.

[0057] like Figure 2 As shown in FIG. 1 , the lithium-ion battery prepared in this embodiment has a specific capacity of 225 mAh / g in the first cycle of charge and discharge at 0.1C. Figure 3 , the efficiency of 100 cycles at 1C is 83.53%.

[0058] Example 2

[0059] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0060] S1 weighs LiNi with a mass ratio of 7:3 0.8 Co 0.1 Mn 0.1 O2 powder and Li 1.3 Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiNi 0.8 Co 0.1 Mn 0.1 O2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.039 mol / ml.

[0061] S2 adds Li2CO3 to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added Li2CO3 is 15% of that of the mixture A.

[0062] S3: The mixture B is co-fired at 700° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as NCM811 / LATP-2.

[0063] The prepared NCM811 / LATP-2 was subjected to XRD detection. Figure 1 As shown in the figure, the peak intensity and position of NCM811 remain unchanged, indicating that the addition of the sacrificial agent inhibits the side reactions of the dual-phase composite cathode during high-temperature co-firing, stabilizes the structure of the dual-phase composite cathode, and there is no sacrificial agent phase.

[0064] like Figure 2 As shown in FIG. 1 , the lithium-ion battery prepared in this embodiment has a specific capacity of 224 mAh / g in the first cycle of charge and discharge at 0.1C. Figure 3, the efficiency of 100 cycles at 1C is 83.42%.

[0065] Example 3

[0066] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0067] S1 weighs LiNi with a mass ratio of 7:3 0.8 Co 0.1 Mn 0.1 O2 powder and Li 1.3 Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiNi 0.8 Co 0.1 Mn 0.1 O2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.039 mol / ml.

[0068] S2 adds Li2C2O4 to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added Li2C2O4 is 15% of that of the mixture A.

[0069] S3: The mixture B is co-fired at 700° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as NCM811 / LATP-3.

[0070] The prepared NCM811 / LATP-3 was subjected to XRD detection. Figure 1 As shown in the figure, the peak intensity and position of NCM811 remain unchanged, indicating that the addition of the sacrificial agent inhibits the side reactions of the dual-phase composite cathode during high-temperature co-firing, stabilizes the structure of the dual-phase composite cathode, and there is no sacrificial agent phase.

[0071] like Figure 2 As shown in FIG. 1 , the lithium-ion battery prepared in this embodiment has a specific capacity of 210 mAh / g in the first cycle of charge and discharge at 0.1C. Figure 3 , the efficiency of 100 cycles at 1C is 53.95%.

[0072] Example 4

[0073] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0074] S1 weighs LiNi with a mass ratio of 7:3 0.8 Co 0.1 Mn 0.1 O2 powder and Li 1.3Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiNi 0.8 Co 0.1 Mn 0.1 O2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.039 mol / ml.

[0075] S2 adds LiOH·H2O to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added LiOH·H2O is 10% of that of the mixture A.

[0076] S3: The mixture B is co-fired at 700° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as NCM811 / LATP-4.

[0077] The prepared NCM811 / LATP-4 was subjected to XRD detection, and the peak intensity and position of NCM811 remained unchanged, indicating that the addition of the sacrificial agent suppressed the side reactions of the dual-phase composite positive electrode during high-temperature co-firing, stabilized the structure of the dual-phase composite positive electrode, and there was no sacrificial agent phase.

[0078] The lithium ion battery prepared in this embodiment has a specific capacity of 218 mAh / g in the first cycle of charge and discharge at 0.1C, and a cycle efficiency of 80.13% for 100 cycles at 1C.

[0079] Example 5

[0080] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0081] S1 weighs LiNi with a mass ratio of 7:3 0.8 Co 0.1 Mn 0.1 O2 powder and Li 1.3 Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiNi 0.8 Co 0.1 Mn 0.1 O2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.039 mol / ml.

[0082] S2 adds LiOH·H2O to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added LiOH·H2O is 15% of that of the mixture A.

[0083] S3: The mixture B is co-fired at 650° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as NCM811 / LATP-5.

[0084] The prepared NCM811 / LATP-5 was subjected to XRD detection, and the peak intensity and position of NCM811 remained unchanged, indicating that the addition of the sacrificial agent suppressed the side reactions of the dual-phase composite positive electrode during high-temperature co-firing, stabilized the structure of the dual-phase composite positive electrode, and there was no sacrificial agent phase.

[0085] The lithium ion battery prepared in this embodiment has a specific capacity of 223 mAh / g in the first cycle of charge and discharge at 0.1C, and a cycle efficiency of 85.19% for 100 cycles at 1C.

[0086] Example 6

[0087] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0088] S1 weighs LiNi with a mass ratio of 7:2.8 0.8 Co 0.1 Mn 0.1 O2 powder and Li 1.3 Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiNi 0.8 Co 0.1 Mn 0.1 O2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.039 mol / ml.

[0089] S2 adds LiOH·H2O to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added LiOH·H2O is 15% of that of the mixture A.

[0090] S3: The mixture B is co-fired at 600° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as NCM811 / LATP-6.

[0091] The prepared NCM811 / LATP-6 was subjected to XRD detection, and the peak intensity and position of NCM811 remained unchanged, indicating that the addition of the sacrificial agent suppressed the side reactions of the dual-phase composite positive electrode during high-temperature co-firing, stabilized the structure of the dual-phase composite positive electrode, and there was no sacrificial agent phase.

[0092] The lithium ion battery prepared in this embodiment has a first cycle charge and discharge at 0.1C, a battery specific capacity of 220 mAh / g, and a 100-cycle cycle efficiency of 81.35% at 1C.

[0093] Example 7

[0094] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0095] S1 weighs LiNi with a mass ratio of 7:3.2 0.8 Co 0.1 Mn 0.1 O2 powder and Li 1.3 Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiNi 0.8 Co 0.1 Mn 0.1 O2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.039 mol / ml.

[0096] S2 adds LiOH·H2O to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added LiOH·H2O is 5% of the mass of the mixture A.

[0097] S3: The mixture B is co-fired at 700° C. for 1.0 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as NCM811 / LATP-7.

[0098] The prepared NCM811 / LATP-7 was subjected to XRD detection, and the peak intensity and position of NCM811 remained unchanged, indicating that the addition of the sacrificial agent suppressed the side reactions of the dual-phase composite positive electrode during high-temperature co-firing, stabilized the structure of the dual-phase composite positive electrode, and there was no sacrificial agent phase.

[0099] The lithium ion battery prepared in this embodiment has a specific capacity of 171 mAh / g in the first cycle of charge and discharge at 0.1C, and a cycle efficiency of 76.38% for 100 cycles at 1C.

[0100] Example 8

[0101] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0102] S1 weighed LiCoO2 powder and Li in a mass ratio of 7:3 1.3 Al 0.3 Ti 1.7(PO3)4 powder and mixed to obtain mixture A, LiCoO2 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.042 mol / ml.

[0103] S2 adds LiOH·H2O to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added LiOH·H2O is 15% of that of the mixture A.

[0104] S3: The mixture B is co-fired at 700° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as LiCoO2 / LATP-1.

[0105] The prepared LiCoO2 / LATP-1 was subjected to XRD detection. Figure 4 As shown, the peak intensity and position of LiCoO2 remain unchanged, indicating that the addition of the sacrificial agent inhibits the side reactions of the dual-phase composite cathode during high-temperature co-firing, stabilizes the structure of the dual-phase composite cathode, and there is no sacrificial agent phase.

[0106] like Figure 5 The lithium-ion battery prepared in this embodiment has a first cycle charge and discharge at 0.1C, and the battery specific capacity is 185 mAh / g. Figure 6 As shown, the efficiency of 100 cycles at 1C is 87.68%.

[0107] Example 9

[0108] The present invention provides a composite positive electrode material for a lithium ion battery and a preparation method thereof, comprising:

[0109] S1 weighed LiFePO4 powder and Li in a mass ratio of 7:3 1.3 Al 0.3 Ti 1.7 (PO3)4 powder and mixed to obtain mixture A, LiFePO4 and Li 1.3 Al 0.3 Ti 1.7 The difference in lithium ion concentration of (PO3)4 is 0.013 mol / ml.

[0110] S2 adds LiOH·H2O to the mixture A and mixes them to obtain a mixture B, wherein the mass of the added LiOH·H2O is 15% of that of the mixture A.

[0111] S3: The mixture B is co-fired at 700° C. for 0.5 h in an air atmosphere, and then naturally cooled to room temperature to finally obtain a dual-phase composite positive electrode material, which is recorded as LiFePO4 / LATP-1.

[0112] The prepared LiFePO4 / LATP-1 was subjected to XRD detection. Figure 7 , the peak intensity and position of LiFePO4 remain unchanged, indicating that the addition of the sacrificial agent inhibits the side reactions of the dual-phase composite cathode during high-temperature co-firing, stabilizes the structure of the dual-phase composite cathode, and there is no sacrificial agent phase.

[0113] like Figure 8 The lithium-ion battery prepared in this embodiment has a first cycle charge and discharge at 0.1C, and the battery specific capacity is 160 mAh / g. Fig. 9 , the efficiency of 100 cycles at 1C is 94.66%.

[0114] Comparative Example 1

[0115] Compared with Example 1, step S2 is omitted in this comparative example.

[0116] The prepared NCM811 / LATP-10 was subjected to XRD detection. Figure 1 As shown in the figure, after high-temperature co-firing at 700°C for 0.5h, the intensity of the strongest peak (003) and the second strongest peak (104) of NCM811 in Comparative Example 1 decreased significantly, indicating that NCM811 participated in side reactions during the high-temperature co-firing process; the layered cracks (006) / (102) and (018) / (110) peaks changed, indicating that the layered structure of NCM811 gradually declined.

[0117] like Figure 2 As shown, the lithium-ion battery prepared in this embodiment has a specific capacity of 102 mAh / g in the first cycle of charge and discharge at 0.1C. Figure 3 , the efficiency of 100 cycles at 1C is 18.27%.

[0118] Comparative Example 2

[0119] Compared with Example 8, step S2 is omitted in this comparative example.

[0120] The prepared LiCoO2 / LATP-10 was subjected to XRD detection. Figure 4 As shown in the figure, after high-temperature co-firing at 700℃ for 0.5h, the intensities of the strongest peak (003) and the second strongest peak (104) of LiCoO2 were greatly reduced, and the peak of Co3O4 appeared, indicating that LiCoO2 participated in side reactions during the high-temperature co-firing process.

[0121] like Figure 5 The lithium-ion battery prepared in this embodiment has a first cycle charge and discharge capacity of 99 mAh / g at 0.1C. Figure 6 As shown, the efficiency of 100 cycles at 1C is 64.75%.

[0122] Comparative Example 3

[0123] Compared with Example 9, step S2 is omitted in this comparative example.

[0124] The prepared LiFePO4 / LATP-10 was subjected to XRD detection. Figure 7 After 700℃ high temperature co-firing for 0.5h, the peak intensity of LiFePO4 decreased significantly, and the peak of Fe2O3 appeared, indicating that LiFePO4 participated in the side reaction during the high temperature co-firing process.

[0125] like Figure 8 The lithium-ion battery prepared in this embodiment has a first cycle charge and discharge at 0.1C, and the battery specific capacity is 101 mAh / g. Fig. 9 , the efficiency of 100 cycles at 1C is 91.24%.

[0126] Comparative Example 4

[0127] Compared with Example 6, in this comparative example, the mass of the added LiOH·H2O is 16% of the mixture A.

[0128] XRD detection of the prepared NCM811 / LATP-11 showed the presence of partial lithium oxide phase.

[0129] The lithium ion battery prepared in this embodiment has a specific capacity of 215 mAh / g in the first cycle of charge and discharge at 0.1C, and a cycle efficiency of 70.20% for 100 cycles at 1C.

[0130] Comparative Example 5

[0131] Compared with Example 7, in this comparative example, the mass of the added LiOH·H2O is 4% of the mixture A.

[0132] XRD analysis of the prepared NCM811 / LATP-12 showed that the intensity of the strongest peak (003) and the second strongest peak (104) of NCM811 were slightly reduced, indicating that certain by-products were generated in the reaction.

[0133] The lithium ion battery prepared in this embodiment has a specific capacity of 165 mAh / g in the first cycle of charge and discharge at 0.1C, and a cycle efficiency of 62.3% for 100 cycles at 1C.

[0134] Comparative Example 6

[0135] Compared with Example 7, in this comparative example, in step S3, the mixture B is co-fired at 700° C. in an air atmosphere for 1.2 h.

[0136] XRD analysis of the prepared NCM811 / LATP-13 showed that the intensity of the strongest peak (003) and the second strongest peak (104) of NCM811 were slightly reduced, indicating that certain by-products were generated in the reaction.

[0137] The lithium ion battery prepared in this embodiment has a specific capacity of 167 mAh / g in the first cycle of charge and discharge at 0.1C, and a cycle efficiency of 66.3% for 100 cycles at 1C.

[0138] Comparative Example 7

[0139] Compared with Example 6, in this comparative example, in step S3, the mixture B is co-fired at 600° C. in an air atmosphere for 0.4 h.

[0140] XRD detection of the prepared NCM811 / LATP-14 showed the presence of partial lithium oxide phase.

[0141] The lithium ion battery prepared in this example has a first cycle charge and discharge at 0.1C, a battery specific capacity of 211 mAh / g, and a 100-cycle cycle efficiency of 71.8% at 1C.

[0142] Example 8

[0143] Compared with Example 1, in this comparative example, the average particle size of LiOH·H2O is 1 μm.

[0144] XRD analysis of the prepared NCM811 / LATP-15 showed that the intensity of the strongest peak (003) and the second strongest peak (104) of NCM811 were slightly reduced, indicating that certain by-products were generated in the reaction.

[0145] By comparing Examples 1-9 and Comparative Examples 1-3, it can be seen that without adding a sacrificial agent, the prepared dual-phase composite positive electrode materials all have by-products generated, resulting in the prepared lithium-ion battery having a low electrochemical activity. By comparing Examples 6, 7 and Comparative Examples 4-7, it can be seen that the amount of sacrificial agent added and the sintering process affect the performance of the prepared battery. If the amount added is too little, a small amount of by-products will be generated. If the amount added is too much, some lithium oxide phases will remain. The above reasons all lead to the low electrochemical activity of the prepared lithium-ion battery. By comparing Example 1 and Comparative Example 8, it can be seen that the particle size of the sacrificial agent will affect its inhibitory effect on NCM811 and LATP. When the particle size is too large, the inhibitory ability is weak.

[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite positive electrode material for a lithium ion battery, characterized in that: The steps include: Weighing and mixing positive electrode material powder and solid electrolyte powder to obtain mixture A, wherein the positive electrode material and the solid electrolyte material are designed to be oxides and the difference in lithium ion concentration is not less than 0.012 mol / ml; Adding a sacrificial agent to the mixture A and mixing them to obtain a mixture B, wherein the amount of the sacrificial agent added is 5% to 15% of the mass of the mixture A; The mixture B is sintered to obtain.

2. The preparation method according to claim 1, characterized in that: The designed positive electrode material is one or more of NCM, lithium cobalt oxide or lithium iron phosphate.

3. The preparation method according to claim 2, characterized in that: The NCM is LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.9 Co 0.05 Mn 0.05 O2 or LiNi 0.6 Co 0.2 Mn 0.2 O2.

4. The preparation method according to claim 1, characterized in that: The designed solid electrolyte material is lithium aluminum titanium phosphate.

5. The preparation method according to claim 1, characterized in that: The designed mass ratio of the positive electrode material to the solid electrolyte material is 7:(2.8-3.2). Weigh the positive electrode material powder and the solid electrolyte powder.

6. The preparation method according to claim 1, characterized in that: The sacrificial agent is lithium hydroxide, lithium carbonate or lithium oxalate.

7. The preparation method according to claim 6, characterized in that: The average particle size of the sacrificial agent is no more than 0.8 μm.

8. The preparation method according to claim 1, characterized in that: The sintering process is: in an oxidizing atmosphere, keeping the temperature at 600-700° C. for 0.5-1.0 h.

9. A composite positive electrode material, characterized in that: The composite positive electrode material is prepared by the preparation method described in any one of claims 1-8.

10. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery is prepared by using the composite positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method for composite positive electrode material used for solid-state lithium ion battery

    CN107017388A

  • Lithium lanthanum zirconium oxide / lithium cobalt oxide composite material and preparation method and application thereof

    CN111697204A

  • Positive electrode material and preparation method thereof, positive plate, battery and electric device

    CN115513437A

  • Positive electrode material and preparation method and application thereof

    CN116130638A

  • Double-layer coated positive electrode material and preparation method thereof, lithium ion battery and vehicle

    CN116722135A